Socio-cultural Factors and Perception of Women Towards Menstruation Restrictions in Siddarthanagar Municipality, Rupandehi - Dhakal, Naba Raj; Thapa, Kavita (THE ACADEMIA, 2025)
Menstruation is purely a biological process- normal vaginal bleeding. However, it is perceived social taboos that restrict the women in various ways in their private and public life. The restrictive practices prevalent in Hindu culture consider the women as impure and unclean in the periods. This research article intends to explore the social and cultural factors that push the women to the position of pollution. In addition, this article also explores the perceptions and experiences of menstruating women. The semi-structured interview schedule has been applied for collecting information from Dogara and Ghanda Tole, Bhairahwa, Rupandehi that comprises both Madhesi and hilly of women aged between 12 to 24, representatively selected using purposive sampling. This research argues that menstruation restrictions, especially from entering into kitchen, worshiping the temples and many more are not followed out of the will of the women. However, Patriarchal mindset of society and family, traditional stereotypes, religious dogma etc are imposed upon women aiming to compel them to follow the discriminatory practices which come out of the sense of fearfulness and shamefulness. The finding of this research is significant for the field of social Science such that it provides an approach to comprehend the social and cultural dimensions of the taboos in the form of menstruation restrictions.